Development of vitellogenin enzyme-linked immunosorbent assay for Asian seabass, Lates calcarifer (Bloch 1790) - Mohd Rashid, Noor Fazielawanie (2012)
Vitellogenin (vtg) is a major protein present abundantly in female fish undergoing oogenesis. In male and immature fish, vtg gene is normally suppressed. However, vtg synthesis can be induced by administration of estrogen hormone (E2). This study was conducted to induce, purify and characterize vtg in E2-treated immature Lates calcarifer. This is important for screening maturity status of this economically important species in a farm. Two-year old immature L. calcarifer (n=10) were given three intraperitoneal injections of 17-β estradiol (E2) at a dose of 2 mg/kg body weight at two days intervals to induce vitellogenesis. Control groups (vitellogenic female and matured male L. calcarifer, n=6) were injected with 0.9% saline only. Blood was collected three days after the last injection and plasma was purified through gel filtration chromatography using Sepachryl HR-300 column, eluted with Tris-HCl pH 8.0. A broad, single symmetrical peak consisting of vtg molecule was produced. Protein concentration was 0.059 mg/ml as determined by Bradford assay using Bovine Serum Albumin (BSA) as standard. The purified protein was electrophoresed on Native PAGE to confirm the purity and determine the molecular weight of putative vtg. The protein appeared as one dimeric circulating form with molecular weight of 545 kDa. In SDS-PAGE under reducing conditions, two major bands appeared at 232.86 and 118.80 kDa and minor bands at 100.60, 85.80 and 39.92 kDa, respectively. The purified vtg was used to generate polyclonal antibody (Abvtg) against vtg and the specificity of antibody was assessed by Western blot analysis. Two major bands were immunoreacted, whereas no cross-reactivity was observed with plasma from non-induced males. Lates calcarifer vtg was found to be phosphoglycolipoprotein as it positively stained for the presence of lipid, phosphorus and carbohydrate using Sudan Black B,methyl green and periodic acid/Schiff reagent solution (PAS), respectively. The amino acid composition was analysed by high sensitivity Amino Acid Analysis (AAA) which showed high percentage of non-polar amino acids (~48%). The polyclonal antibody generated was used to develop a competitive enzyme-linked immunosorbent assay (ELISA) for quantifying plasma vtg concentration. Working ranges of the assay were from 31.2 to 1000 ng/ml with a sensitivity of 6.9 ng/ml. The ELISA demonstrated precision with intra-(< 8.4, n=9) and inter-assay (<12.1, n=5) variations at 90, 80 and 50% of binding. Serial plasma dilutions from vitellogenic females and E2-treated immature L. calcarifer were paralleled to the vtg standard curve (purified vtg)as analyzed by Analysis of Covarians (ANCOVA) (p > 0.05). No crossreaction was detected from male plasma dilution, thus validating that the assay quantified plasma vtg in L. calcarifer. The accuracy and sensitivity of vtg measurement by immunoassay has broad application in aquaculture for managing fish broodstock in captivity. The present study successfully isolated and characterized vtg in induced immature L. calcarifer. Analysis of vtg using Abvtg is proposed as indicator in determining female maturity stage.